Characterization of Heavy-Metal-Removal Bacteria From The Persian Gulf - Zolgharnein, Hossein (2005)
The study was carried out to isolate and screen high heavy metals resistant bacteria from Persian Gulf and enclosed industrial areas within 241,000 km2. A total of 35 heavy metal resistant bacteria strains were identified from sediment and water samples collected. The resistance and biological capacity of the isolated bacteria were tested in a new formulated media, minimal salt solution (M.S.S), that mimics seawater. Isolated bacteria responded to media supplemented in range 0.5 to 2 mM of Zn, Cd, Cu and Pb by showing a prolonged lag phase and by decreasing growth rate. Bacteria isolates, in the form of free or immobilized cells, are able to remove lead, copper, zinc and cadmium from solution. Removal of lead and cadmium from solution by some bacteria was very efficient, about 120 mglg dry weight as high as 90%. Isolates tested presented distinct uptake capacities and the best results were obtained for Delftia tsuruhatensis and Pseudornonas AU3411 respectively.The diversity of isolated bacteria was examined by the phylogenetic analysis of 16s rRNA gene sequences. The phylogenetic analyses of the sequences revealed seven main taxonomic lineages. The phylogenetic tree illustrated discrimination between isolated bacteria from wastewater, industrials areas and marine environment. Some Pseudornonas strains isolated from marine environment were well differentiated from those of industrial wastewater. Members of the genera Delftia and Bacterium formed a monophyletic group within the subdivision of the class. There was a clear differentiation between two groups of Pseudornonas and other groups of bacteria in the phylogenetic tree. The isolated bacteria were tested for the occurrence of plasmid using the modified alkaline lysate method. The study revealed that the frequency of the occurrence of plasmid in the heavy metals resistance bacteria was more than in the common bacteria. Multiple forms of plasmids were observed in 66% of the plasmidcarrying strains. Isolates bacteria from industrials wastewater showed the highest plasmid incidence (84.6%). In the marine environment there was a slightly higher incidence of plasmid in bacteria isolated from sediments (55.5%) compared to the water sample of the same origin (53.8%). Scanning Electron Microscope (SEM) analyses showed Pseudornonas sp. accumulated heavy metals in the cell wall and along the external cell surfaces. This suggested that heavy metals uptake involves both surface phenomena and diffusion. Energy Dispersive X-ray (EDX) analysis confirmed heavy metals on the bacteria cell surface which was reported by SEM.